Propriedades e aplicabilidade na construção civil da cerâmica composta por catalisador de síntese de metanol, lama vermelha e escória siderúrgica - Alarcon, Reinaldo Hidalgo Guidolin (2018)
Thirteen series of ceramic composites were made using methanol synthesis catalyst, red mud from bauxite processing and steel slag, with the subsequent realization of tests and feasibility analyzes of the use as civil construction material. The specimens (CPs) were made with 20 g in a 20 x 60 mm mold and 5 MPa uniaxial press. The CPs were sintered at temperatures of 900, 1000, 1050, 1100 and 1150 ° C for 6 hours. Moisture, density, fire loss, FRX, XRD, MEV / EDS, linear retraction, water absorption, flexural strength, leaching and solubilization were performed to characterize the raw materials and the ceramic material originated. The results demonstrate the feasibility of the use of components for the production of ceramic materials applicable to civil construction. The composition that presented the best result reached 25.98 MPa of flexural strength, 8.80% of water absorption, 20.14% of linear retraction of burn and 3.46 of density. The result of the leaching indicates that there was immobilization of the heavy metals analyzed, present in the composition of the specimens. Compared to standards NBR 7.170, NBR 13.818 and NBR 15.270-2, water absorption and resistance aspects met the requirements for making ceramic tiles for Group BIIa, Class A, B and C solid bricks, and ceramic blocks for structural masonry.